In vivo modulation of 4E binding protein 1 (4E-BP1) phosphorylation by watercress: a pilot study - Syed Alwi, Sharifah S. (2010)
Dietary intake of isothiocyanates (ITC) has been associated with reduced cancer risk. The dietary phenethyl ITC (PEITC) has previously been shown to decrease the phosphorylation of the translation regulator 4E binding protein 1 (4E-BP1). Decreased 4E-BP1 phosphorylation has been linked to the inhibition of cancer cell survival and decreased activity of the transcription factor hypoxia-inducible factor (HIF), a key positive regulator of angiogenesis, and may therefore contribute to potential anti-cancer effects of PEITC. In the present study, we have investigated the in vitro and in vivo effects of watercress, which is a rich source of PEITC. We first demonstrated that, similar to PEITC, crude watercress extracts inhibited cancer cell growth and HIF activity in vitro. To examine the effects of dietary intake of watercress, we obtained plasma and peripheral blood mononuclear cells following the ingestion of an 80 g portion of watercress from healthy participants who had previously been treated for breast cancer. Analysis of PEITC in plasma samples from nine participants demonstrated a mean maximum plasma concentration of 297 nM following the ingestion of watercress. Flow cytometric analysis of 4E-BP1 phosphorylation in peripheral blood cells from four participants demonstrated significantly reduced 4E-BP1 phosphorylation at 6 and 8 h following the ingestion of watercress. Although further investigations with larger numbers of participants are required to confirm these findings, this pilot study suggests that flow cytometry may be a suitable approach to measure changes in 4E-BP1 phosphorylation following the ingestion of watercress, and that dietary intake of watercress may be sufficient to modulate this potential anti-cancer pathway.